Social Interaction of Adolescents: An Impact Analysis of Phubbing Behavior - Magfiroh, Lailatul; Oktaviani, Maya; Kabbaro, Hurriyyatun (Asosiasi Asesmen Pendidikan (AAP), 2024)
For adolescents, the need to interact is very important amidst the development of smartphone use for social, emotional, and psychological development has an influence on prioritizing and valuing direct social interaction. This study aims to determine the effect of phubbing behavior on social interaction in adolescents at SMP Negeri 74 Jakarta. The study was conducted using an associative quantitative research method with a data collection method using a questionnaire. The location of the study was at SMP Negeri 74 Jakarta and took place from May 2024 - June 2024. The respondents in this study were 150 adolescents who met the specified criteria. The data collection technique in this study used a nonprobability sampling technique with a purposive sampling approach, where the sample was used if it met the following criteria: adolescents aged 12-16 years calculated from the age of the study period before May 2024 and Have a smartphone and actively use a smartphone. This study used the Social Interaction Skills (SIS) instrument by Lamash et al., (2023) and had a reliability coefficient of 0.890 for social interaction and the Generic Scale of Phubbing (GSP) Chotpitayasunondh & Douglas, (2018) reliability coefficient of 0.769 for phubbing behavior. The data analysis technique used was a significant regression test, which produced a Fhit value (b / a) = 16.782 and a Sig. value of 0.000 <0.05. The results showed that phubbing behavior had an effect on social interaction in adolescents at SMP Negeri 74 Jakarta. Furthermore, the results of the determination coefficient were 0.102, so that the contribution of phubbing behavior to social interaction was 10.2%. Adolescents who have high phubbing behavior will have low social interaction. The results of this study are to raise awareness of the negative impacts of phubbing on social interactions, especially schools, providing counseling services to students who are identified as being dependent on digital devices or who show signs of difficulty in social interactions. Counselors can help students develop social skills.